2000
DOI: 10.1002/(sici)1097-0142(20000515)88:10<2239::aid-cncr6>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

High expression of vascular endothelial growth factor is associated with liver metastasis and a poor prognosis for patients with ductal pancreatic adenocarcinoma

Abstract: BACKGROUND Vascular endothelial growth factor (VEGF), a recently identified growth factor with significant angiogenic properties, is a multifunctional angiogenic cytokine that is expressed in many tumors. High VEGF expression has been shown to correlate with the incidence of metastasis and poor prognosis in various cancers. In this study, the authors investigated VEGF expression and microvessel density (MVD) in ductal pancreatic adenocarcinoma and examined the correlations among VEGF expression, clinicopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
201
3
8

Year Published

2001
2001
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(224 citation statements)
references
References 29 publications
11
201
3
8
Order By: Relevance
“…In fact, significant downregulations of these mRNA expression levels were demonstrated in the retrovirally infected thyroid cell lines expressing the antisense HMGA2 (Vallone et al, 1997). Considering that the overexpression of the AP-1 (Tessari et al, 1999;Meggiato et al, 2003), VEGF (Seo et al, 2000), MMP-1 (Ito et al, 1999), and MMP-3 (Bramhall et al, 1996) has been demonstrated in human pancreatic cancer, together with our results, the interactions among these molecules may play an important role in pancreatic neoplastic transformation in vivo, Further studies, including the determination of expression levels of these molecules in tissue samples, have yet to be carried out to further clarify this issue. Conversely, the HMGA2 gene has recently been shown not to be necessary for the malignant transformation of thyroid cells in vivo (Scala et al, 2001).…”
Section: Discussionsupporting
confidence: 66%
“…In fact, significant downregulations of these mRNA expression levels were demonstrated in the retrovirally infected thyroid cell lines expressing the antisense HMGA2 (Vallone et al, 1997). Considering that the overexpression of the AP-1 (Tessari et al, 1999;Meggiato et al, 2003), VEGF (Seo et al, 2000), MMP-1 (Ito et al, 1999), and MMP-3 (Bramhall et al, 1996) has been demonstrated in human pancreatic cancer, together with our results, the interactions among these molecules may play an important role in pancreatic neoplastic transformation in vivo, Further studies, including the determination of expression levels of these molecules in tissue samples, have yet to be carried out to further clarify this issue. Conversely, the HMGA2 gene has recently been shown not to be necessary for the malignant transformation of thyroid cells in vivo (Scala et al, 2001).…”
Section: Discussionsupporting
confidence: 66%
“…27 In patients with such neoplasia, VEGFA expression in the tumor and high serum concentration are significantly correlated to a decreased median survival time 37,38 and to metastasis progression, especially to the liver. 28 The correlation between VEGFA expression and the survival remains significant even after a surgery putatively considered as curative. 39 These results are consistent with the discovery that microvessel density and vascular proliferation index were significantly associated with larger tumor size and lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with normal pancreas and chronic pancreatitis, VEGF and its receptors were overexpressed in pancreatic cancer [73]. Seo Y et al demonstrated that 93% of ductal pancreatic adenocarcinomas were positive for VEGF protein [74]. A recent study shows a positive expression rate of VEGF 77% in pancreatic cancer tissues and 15% in adjacent normal pancreatic tissues [75].…”
Section: Pancreatic Cancermentioning
confidence: 99%